Hydroalcoholic extract of Haematoxylum brasiletto protects Caenorhabditis elegans from cadmium-induced toxicity - Margareth Duran-Izquierdo; María Taboada-Alquerque; Lucellys Sierra-Marquez; Neda Alvarez-Ortega; Elena Stashenko; Jesus Olivero-Verbel (BMC, 2022)
Highlights Most secondary metabolites tentatively identified in H. brasiletto are homoisoflavones. Hidroalcoholic extract of H. brasiletto protects C. elegans from Cd toxicity The extract diminished Cd-induced damage to reproduction, growth, and locomotion. Cd-induced oxidative stress and translocation of DAF-16 are blocked by the extract.